Insights of numerical simulations of magnetohydrodynamic squeezing nanofluid flow through a channel with permeable walls - Khan, Kashif Ali; Raza, Nauman; İnç, Mustafa (Keai Publishing Ltd, 2021)
An analysis related to the transport of nanofluid that is confined in a channel between two orthogonal permeable walls will be investigated with the help of two numerical techniques. With the aid of the reasonable similarity changeover; the said model will be shaped into the desired non-linear equation whose behavior will be explained analytically as well as graphically where the functioning of three disparate variables such as magnetic parameter, permeable Reynold number, and channel permeable ratio will be explained precisely. The said model has been controlled by the homotopy analysis method (HAM) and then, compared through an efficient numerical method named shooting method (ShM). The profiles show that increases in the magnetic parameter decline the nanofluid flow velocity, whereas magnitude-wise raise is shown in each axial velocity profile. The radial profile raises while getting variation in wall expansion parameter from negative to positive. For the entire domain, the rate of change in velocity description enhances at the center while reduces at the surfaces. And the outcomes disclose that the wall permeable ratio has a significant impact on the solutions. Since the zero value of wall ratio refers to the particular type that Terrill has discussed. (C) 2021 Beihang University. Publishing services by Elsevier B.V. on behalf of KeAi Communications Co. Ltd.
Keywords: Homotopy analysis method; Orthogonal walls; Nanofluid; Similarity changeover; Wall ratio factor